2016
DOI: 10.1038/ncomms11165
|View full text |Cite
|
Sign up to set email alerts
|

Mouse model of chromosome mosaicism reveals lineage-specific depletion of aneuploid cells and normal developmental potential

Abstract: Most human pre-implantation embryos are mosaics of euploid and aneuploid cells. To determine the fate of aneuploid cells and the developmental potential of mosaic embryos, here we generate a mouse model of chromosome mosaicism. By treating embryos with a spindle assembly checkpoint inhibitor during the four- to eight-cell division, we efficiently generate aneuploid cells, resulting in embryo death during peri-implantation development. Live-embryo imaging and single-cell tracking in chimeric embryos, containing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
358
2
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 383 publications
(386 citation statements)
references
References 46 publications
20
358
2
6
Order By: Relevance
“…From blastocyst stage on aneuploid cells progressively deplete, and mosaic embryos have full developmental potential as long as they contain sufficient euploid cells [18]. With aneuploid cells preferably seggregating into the trophectoderm, it appears reasonable to assume that mosaicism rates will increase with number of trophectoderm biopsies performed.…”
Section: Discussionmentioning
confidence: 99%
“…From blastocyst stage on aneuploid cells progressively deplete, and mosaic embryos have full developmental potential as long as they contain sufficient euploid cells [18]. With aneuploid cells preferably seggregating into the trophectoderm, it appears reasonable to assume that mosaicism rates will increase with number of trophectoderm biopsies performed.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this finding, a recent study by Bolton and colleagues concluded that there was no evidence for preferential allocation of aneuploid cells in mosaic mouse embryo models (51). To investigate both aneuploid cells' fate and the developmental potential of mosaic embryos, Bolton and colleagues generated a mouse model with euploid-aneuploid chromosome mosaicism using the drug Reversine to inhibit SAC protein monopolar spindle 1-like 1 (Mps1) kinase during the 4-to 8-cell stage transition.…”
Section: Aneuploidies and Blastocyst Differentiationmentioning
confidence: 91%
“…Mosaicism is postulated to originate from improper expression of cell cycle checkpoint genes during the primary mitotic cell divisions in the early embryo when maternal transcripts control the cell cycle [9]. At later cleavage stages, the embryonic genome takes over and may be able to overcome mosaicism by allowing the proliferation of normal cells and the inhibition of mitotic activity in abnormal ones [11][12][13]. Such a process is supported by data showing that chromosomal mosaicism is far lower at the blastocyst stage (days 5-6) as compared to the cleavage stage (day 3).…”
Section: Introductionmentioning
confidence: 99%